Quality of life, level of anxiety and level of depression among former artistic gymnasts, former gymnasts from other sports and non-athletes - Dimitriadou, K.; Dallas, C.; Papouliakos, S.; Dallas, G. (Science of Gymnastics Journal, 2022)
Involving people in physical activity or sport provides some health-related benefits and has a positive effect on their quality of life (QoL). However, high level athletes experience anxiety to cope with the high demands of the sport. The purpose of the study was to assess the QoL, level of anxiety (STAI) and level of depression (BDI) among former artistic gymnasts, former athletes from other gymnastics sports (acrobatic, rhythmic, gymnastics for all) and non-athletes. Secondly, it aimed to investigate if there are gender differences within the groups on the aforementioned variables. 114 healthy people (75 women and 39 men) were involved in the present study with a mean age 27.11 ± 9.92 years. The sample was divided into 3 different groups (1st group: 39 former artistic gymnasts (FAG); 2nd group: 53 former gymnasts from other gymnastic sports (GOS), and 3rd group: 22 non-athletes (CG). Participants were asked to complete three different questionnaires in order to assess their QoL, STAI, and BDI. Statistical analysis showed no significant differences on QoL and STAI, whoever a statistically significant difference was found between groups on BDI (p <.05). No main effect was found on gender. Further, results revealed that former gymnasts, regardless of the type of sport, have better QoL, lower level of STAI and BDI compared to non-athletes. In conclusion, former gymnasts, even after years of absence from the sport, report better QoL, and have a lower level of STAI and BDI than non-athletes.